Nilai Siri’ dan Pesse dalam Kebudayaan Bugis-Makassar, dan Relevansinya terhadap Penguatan Nilai Kebangsaan - Badewi, Muhamad Hadis (JSW (Jurnal Sosiologi Walisongo), 2019)
The presence of cultural values in each ethnic group is a inevitability, and certainly has a large contribution to the strengthening of national values in Indonesia, so the culture held by the Bugis-Makassar community, which is trying to be explored in this article. Siri 'and pesse are the two main values in the Bugis-Makassar culture, which have the underlying nature of other core values. The question is about the relevance of the values of siri and pesse toward the strengthening value of Indonesian nationality. To answer this question, library research is conducted using qualitative methods. From the research it was found that, siri’and pesse values have strong relevance if they are associated with efforts to strengthen national values in Indonesia, because siri’ and pesse are values born from the womb of Indonesian culture, which contain humanity and social solidarity.